Influence of selective stimulation of the right ventricle on electric and mechanical myocardial disynchrony - A. E. Komlev; V. N. Shitov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2021)
Relevance. Prolonged apical stimulation of the right ventricle can lead to the development of interventricular and intraventricular dyssynchrony. Selective (alternative) stimulation of various parts of the interventricular septum due to a more physiological propagation of the excitation wave makes it possible to prevent the deterioration of the mechanical function of the myocardium associated with constant pacing.Purpose. To study the dynamics of indicators of electrical and mechanical ventricular dyssynchrony in the traditional (apical) and alternative with the installation of a right ventricular electrode in the interventricular septum or the outlet tract of the right ventricle in patients with constant pacing in the early and late postoperative period.Materials and methods. Were included 73 patients (mean age 61.0 ± 2.5 years) with indications for continuous cardiac pacing without signs of heart failure above 2 FC according to NYHA and previous Q-forming myocardial infarction. Patients of group 1 (n = 39) were implanted with a pacing ventricular electrode in the middle section of the interventricular septum (subgroup 1A, n = 25) or in the outflow tract of the right ventricle (subgroup 1B, n = 14). The control group 2 included 34 patients with electrode implantation in the apex of the right ventricle.Results. The time of pre-ejection from the right and left ventricles before and after implantation did not differ in group 1 and significantly differed in group 2 (25 ± 3 ms and 50 ± 6 ms, p < 0.05). There was no significant difference in the parameters of ventricular remodeling between the groups within 2 years, but there was a tendency towards a lower value of the left ventricular ejection fraction (59 ± 6 % and 50 ± 2 %, p = 0.05) and a higher frequency of mitral regurgitation 2 degree and higher in patients in the apical stimulation group. Within the group of alternative stimulation, after 2 years of follow-up, there was a tendency towards a smaller value of the delay time of systolic contraction between the basal segments of the free wall of the right ventricle and the interventricular septum during stimulation of the outflow tract compared with stimulation of the middle part of the interventricular septum (30 ± 8 ms and 38 ± 10 ms , p = 0.05).Conclusions. Alternative stimulation of the right ventricle compared with the apical is characterized by a lower degree of interventricular dyssynchrony both immediately after surgery and in the long-term period. New echocardiographic technologies, including tissue myocardial Doppler ultrasonography, make it possible to quantify the indicators of systolic and diastolic myocardial function and various parameters of dyssynchrony.Conclusion. To assess the physiology, clinical efficacy and safety of the new method of stimulating the interventricular septum, a more thorough study of the severity of intra- and interventricular dyssynchrony, indicators of global and regional systolic and diastolic function of the left and right ventricles is necessary.